Combined Effect of Nano-SiO2 and Nano-Al2O3 on Improving the Tribological Properties of Kevlar Fabric/Phenolic Laminate in Water. Issue 1 (2nd January 2016) - Liu, Ning; Wang, Jianzhang; Yang, Jie; Han, Gaofeng; Yan, Fengyuan
ABSTRACT: The combined effect of nano-SiO2 and nano-Al2 O3 as fillers on the tribological properties of Kevlar fabric/phenolic laminate (KFPL) in water was investigated. Results showed that the single addition of nano-SiO2 at a proper content decreased the friction coefficient of KFPL to an ultralow value at the cost of an increased wear rate. The single addition of nano-Al2 O3 at a proper content reduced the wear rate of KFPL with fluctuation in the friction coefficient curve. The combined addition of nano-SiO2 and nano-Al2 O3 not only endowed KFPL with an ultralow friction coefficient originated from nano-SiO2 but also improved the wear resistance. This means that the combined addition of nano-SiO2 and nano-Al2 O3 can have positive effects and inhibit their negative aspects to some extent.